English Writing For Publication In International Journals: Basic Criteria In Globalization Era - Ladjel , Karima; Kharkhache , Souhila; Ladjel , Djelloul (El Omda in Linguistics and Discourse Analysis, 2023)
Publishing research articles in international journals has become a precondition to PhD graduation in higher education. In the era of globalization, non-native English PhD students devote much scholarly attention to English writing for publication purposes to share and author their own academic researches for international journals. Thus, this paper aims to demystify the most important requirements of English writing for publication and draw some strategies to successfully publish written English manuscripts in international journals. Along this line of thought, a documentary analysis of 12 different research manuscripts of non-native English academics was undertaken. To cross-check the data, a questionnaire was directed to the manuscripts’ owners and the peer reviewers of journals. The findings reveal that manuscripts which are successfully accepted for publication have features related to both macro and micro criteria. The former includes the procedural strategies that allow manuscripts to be highly and immediately accepted from the first sight such as the originality or timeliness of the work, its direct relevance, appropriateness and interest to the journal targeted, and its effective contributions and solutions to the new emerging era problems. The latter incorporates the specific details and segments that reviewers spot at the second sight such as maintaining coherent and cohesive texts, using authentic and well-cited references, providing relevant arguments, framing data to appeal to different audiences, discussing and synthesizing the results. Depending on these findings, a number of recommendations are provided to remediate the situation. Résumé La publication d'articles de recherche dans des revues internationales est devenue une condition préalable à l'obtention d'un doctorat dans l'enseignement supérieur. À l'ère de la mondialisation, les doctorants non natifs anglais consacrent une grande attention scientifique à l'écriture en anglais à des fins de publication pour partager et rédiger leurs propres recherches universitaires pour des revues internationales. Ainsi, cet article vise à démystifier les exigences les plus importantes de l'écriture anglaise pour la publication et à élaborer quelques stratégies pour publier avec succès des manuscrits écrits en anglais dans des revues internationales. Dans cette ligne de pensée, une analyse documentaire de 12 manuscrits de recherche différents d'universitaires non natifs anglais a été entreprise. Pour recouper les données, un questionnaire a été adressé aux propriétaires des manuscrits et aux pairs examinateurs des revues. Les résultats révèlent que les manuscrits qui sont acceptés avec succès pour publication présentent des caractéristiques liées à la fois aux critères macro et micro. Le premier comprend les stratégies procédurales qui permettent aux manuscrits d'être hautement et immédiatement acceptés dès le premier regard, telles que l'originalité ou l'actualité du travail, sa pertinence directe, son adéquation et son intérêt pour la revue ciblée, et ses contributions et solutions efficaces aux nouveaux problèmes de l'ère émergente. Ce dernier intègre les détails et segments spécifiques que les examinateurs repèrent au second regard, tels que le maintien de textes cohérents et cohésifs, l'utilisation de références authentiques et bien citées, la fourniture d'arguments pertinents, la formulation de données pour plaire à différents publics, la discussion et la synthèse des résultats. En fonction de ces résultats, un certain nombre de recommandations sont fournies pour remédier à la situation.